Forensic characteristics of criminal offences against justice committed by professional participants in legal proceedings - Ye. Yu. Sup (Bulletin of Kharkiv National University of Internal Affairs)
The article emphasises that criminal offences against justice committed by professional participants in justice are characterised by a specific intent, which is to violate the principles of justice, undermine confidence in law enforcement agencies and the judicial system, and also to cause harm to both victims and society as a whole. Given these features, it is substantiated that the development of methods for investigating such offences is one of the main tasks on the way to counteracting these facts of criminal behaviour.